Integrasi Bioremediasi Limbah Peternakan Sapi dan Kultivasi Mikroalga Chlorella vulgaris dan Chlorella pyrenoidosae - Afriyanti Azhar; Abdi Dharma; Armaini armaini; Zulkarnain Chaidir; Syafriza Yanti; Nasril Nasir (LLDIKTI Wilayah X, 2017)
Dairy manure that functioned as organic fertilizer has potential impact as environmental destructive waste because the absorption of inorganic nutrients in the fertilizer. On the other hand, microalgae growth is hindered by the high cost of culture, whereas organic and inorganic nutrient requirements. Dairy manure have the potential for microalgae nutrients, but are hindered by turbidity levels. Its has been tested for dilution dairy manure and treatments on fluorescence and sunlight sources and the addition of urea commercial fertilizer to absorbs organic and inorganic nutrients. Its prove the integration of bioremediation of dairy manure and microalgae cultivation Chlorella pyrenoidosa and Chlorella vulgaris can be performed and also serves as a source of caratenoid (chlorophyll)